Penerapan Problem Based Learning dalam Pembelajaran IPS untuk Membangun Kesadaran Sosial Siswa Sekolah Dasar - badriyah, Laila (Universitas Sulawesi Barat, 2025)
This Study explores how the implementation of the problem Based Learning (PBL) model in Social Studies (IPS) instruction can faster social awarenes among elementary school students. Using a literature review approach, the study examines a range of recent journals, academic articles, and books relevant to the topic. The reviewed literature indicates that Social Studies plays a crucial role in helping students understand social phenomena, develop empathy, and build a sense of responsibility toward their surrounding community. However, Social Studies learning in many elementary classrooms is still dominated by teacher centered methods, which limit students’ opportunities to engage actively in disscussions, investigate real issues, and think critically. The PBL model offers an alternative approach by positioning real-life problems as the foundation of the learning procces. Through collaborative inquiry, group discussions, and guided problem-solving, students gain learning experiences that are meaningful and closely connected to everyday social realities. Findings across several studies show that PBL enhances students’ motivation, critical thinking, cooperation, and sensitivity to social issues. Therefore, integrating PBL into Social Studies instruction serves as an effective strategy not only for strengthening social awareness but also for shaping students’ character in a consistent and sustainable manner. This review provides a theoretical foundation for teachers who wish to design Social Studies lessons that are more participatory, reflective, and relevant to students’ social development.